Split payment narzędziem wspierającym proces uszczelnianie systemu podatkowego – za i przeciw - Piotrowska, Iwona; Ćwiąkała-Małys, Anna; Karpińska, Marzena (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
Split payment is another tool supporting effective limitation of irregularities in the tax system particularly in the fight against VAT tax frauds. Entrepreneurs may use, in case of any doubts according to reliability of trading partners (suppliers), a split payment mechanism of net payment and VAT tax amount from an invoice.  The freedom of choice of this form of payment for the invoice may secure a tax payer form possible sanctions and responsibility in case of unconscious parting in VAT carousel. Implementing a mechanism of split payment is to improve tax payments to the budget. For entrepreneurs and financial institutions (banks and credit unions) it may cause some  organizational problems at the beginning from the point of view of small and average businesses it  may influence accounting liquidity. The aim of this article is to present a Polish mechanism of split payment and some solutions  used in European Union countries with forecasted economic results from the point of view of entrepreneurs and tax system.
Keywords: VAT tax; split payment mechanism; tax gap